Impact of Various Regimens of Rhythmic Extreme Cold Exposures on Hormone and Lipid Content in Blood Serum of Young and Aged Rats - Kulik, Volodymyr V.; Babiichuk, Georgiy O.; Babiichuk, Vladyslav G.; Malova, Natalya G.; Sirotenko, Larisa A. (Problems of Cryobiology and Cryomedicine, 2019)
At present, there is a close relationship between age-related changes in the endocrine system, metabolic disorders and the development of diseases of internal organs, characteristic of the elderly. Rhythmic extreme cold influence (RECI) (–120°C) are a powerful physiotherapeutic procedure that activates the body's adaptive reserves. However, in opposition the high therapeutic efficacy of the RECI, in some cases the use of extreme cooling, especially in the elderly, is accompanied by the occurrence of side effects. Therefore, the effect of different modes of RECI on the content of hormones and lipids in the blood serum of young and old rats was studied. It has been established that in the young and old animals the use of RECI in temperature regimes (–120°C; –120°C; –120° C) and (–60°C; –120°C; –120°C) led to stable stimulation of the thyroid, adrenal and reproductive system in comparison with the (–60°C; –60°C; –60°C). At the same time, the regime (–60°C; –120°C; –120°C) had a "milder" effect on the lipid profile of the blood serum of young and old rats, since it was not accompanied by a pronounced stress reaction of the organism in the form of hyperlipidemia. Probl Cryobiol Cryomed 2019; 29(3): 206–220.